MOTIVASI BERPRESTASI DALAM NOVEL NEGERI 5 MENARA - Syarifah, Laili (Wahana Islamika: Jurnal Studi Keislaman, 2017)
To achieve the results of a goal requires an encouragement. The power that is the driving force is called motivation, which shows a condition in the individual who drives and moves the individual to carry out an activity to achieve a goal. Motivation underlies all individual behaviors, as well as the learning process undertaken by students. Learning is a long process which has been carried out for years. Learning requires motivation, especially achievement motivation, so that it can encourage students to give their best. This type of research is library research, which is an attempt to obtain data using library resources. The types of data used in this study are primary data and secondary data. In analyzing the data that has been collected, the author uses several methods of analysis, namely descriptive methods and content analysis methods. In the novel Negeri 5, Menara Alif was able to carve out achievements by being elected as a Student Speaker. Chosen as a speaker is a long journey that is the result of rigorous selection and observation of speech and language skills. Alif's desire arose when a year before the King was chosen as a speaker when he welcomed the Egyptian Ambassador.